Transient gene expression in serum-free suspension-growing mammalian cells for the production of foot-and-mouth disease virus empty capsids - Mignaqui, Ana Clara; Ruiz, Vanesa; Perret, Sylvie; St-Laurent, Gilles; Chahal, Parminder Singh; Transfiguracion, Julia; Sammarruco, Romina Ayelén; Gnazzo, Victoria; Durocher, Yves; Wigdorovitz, Andres (PLOS, 2019)
Foot-and-mouth disease (FMD) is a highly contagious disease of cloven-hoofed animals. It produces severe economic losses in the livestock industry. Currently available vaccines are based on inactivated FMD virus (FMDV). The use of empty capsids as a subunit vaccine has been reported to be a promising candidate because it avoids the use of virus in the vaccine production and conserves the conformational epitopes of the virus. In this report, we explored transient gene expression (TGE) in serum-free suspension-growing mammalian cells for the production of FMDV recombinant empty capsids as a subunit vaccine. The recombinant proteins produced, assembled into empty capsids and induced protective immune response against viral challenge in mice. Furthermore, they were recognized by anti-FMDV bovine sera. By using this technology, we were able to achieve expression levels that are compatible with the development of a vaccine. Thus, TGE of mammalian cells is an easy to perform, scalable and cost-effective technology for the production of a recombinant subunit vaccine against FMDV.